Linking Item Analysis to Teaching and Learning: What English Test Data Tell Us about Teachers’ Competencies : Penelitian - Suharyadi, Suharyadi; Kusumaningrum, Shirly Rizki (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study examines the psychometric qualities of a tryout test administered to 283 in-service English teachers in Indonesia, using Classical Test Theory (CTT) procedures. The analysis focused on five indices: item validity, discrimination, difficulty, distractor functioning, and item utilization. Results revealed several weaknesses in the test design. Only 46% of items demonstrated acceptable validity, while 54% failed to align meaningfully with the overall construct of teacher competence. More than half of the items showed poor discrimination, limiting the test’s ability to differentiate high- and low-performing teachers. Difficulty levels were skewed, with 72% of items categorized as easy, thereby restricting the measurement of higher-order thinking skills. Distractor analysis indicated that three-quarters of options were non-functioning, reducing diagnostic value. Consequently, only 9% of items could be retained without revision. Despite these shortcomings, the findings provide useful insights into teacher competencies. While basic linguistic and pedagogical knowledge was well represented, higher-order professional skills such as inference, synthesis, and applied pedagogy were under-assessed. These results highlight the importance of strengthening assessment literacy and integrating item analysis into teacher professional development.